Simplified tax system and its development prospect in small businesses (Путеводитель предпринимателя)
The specific tax treatments for small businesses are considered in the scientific article. The global preferential taxation practice for small sized business entities is presented. Peculiarities of the simplified taxation system application in accordance with the Internal Revenue Code of Russian Federation. The article represents economic policy of tax reforming conducted by the government and ways of it improvement.